Pragmatic virtual fragment-based ligand design - Gastreich, Marcus (Henry Stewart Talks, 2011)
Computational chemistry for fragment replacement, fragment evolution/growing/merging & linking, Bioisostere replacement, Software assistance for SAR optimisation for medicinal chemists, Lead optimisation software